Application of auricular acupoint scraping therapy in postoperative patients with lower extremity fracture (耳穴推刮术在下肢骨折术后患者中的应用) - GUI Huiqiong (桂辉琼); WANG Yihua (王一华); YUAN Qingna (袁庆娜); JI Chen (冀晨); YANG Yihua (杨毅华) (中西医结合护理)
Objective To observe the effect of auricular acupoint scraping therapy on postoperative pain and sleep quality of patients with lower extremity fracture. Methods Totally 70 cases of patients undergoing surgery for lower limb fracture were randomly divided into control group and observation group, with 35 cases in each group. The control group received routine treatment and nursing measures, while the observation group was given auricular acupoint scraping therapy based on the routine treatment and nursing measures. Visual analog pain scale (VAS), Pittsburgh Sleep Quality Index (PSQI) score and patient satisfaction before and after treatment were compared between the two groups. Results There was no significant difference in VAS and PSQI scores between two groups before surgery (P＜0. 05). The VAS scores of observation group was significantly decreased compared with those in the control group at 6h, 12h, 24h, 48h and 72h after surgery(P＜0. 05). The PSQI scores of the observation group were significantly decreased compared with those in the control group at 48 h and 72h after surgery (P＜0. 01). The satisfaction degree of the observation group was higher than that of the control group (P＜0. 01). No treatment-related adverse reactions were observed in two groups. Conclusion The auricular acupoint scraping therapy is effective to reduce the postoperative pain and improve the sleep quality of patients undergoing surgery for lower extremity fracture. (目的 观察耳穴推刮术对下肢骨折术后患者疼痛和睡眠质量的影响。方法 选取下肢骨折术后患者70例, 按照随机数字表法分为对照组和观察组, 每组35例。对照组采取常规治疗和护理措施, 观察组在对照组基础上开展耳穴推刮疗法。比较2组患者治疗前后不同时间段内视觉模拟疼痛评分(VAS)、匹兹堡睡眠质量指数量表(PSQI)评分及患者满意度。结果 术前两组患者的VAS、PSQI评分比较, 差异无统计学意义(P＞0. 05)。观察组患者术后6 h、12h、24h、48h、72 h VAS评分低于对照组, 差异有统计学意义(P＜0. 05)。观察组术后48 h、72 h PSQI评分低于对照组, 差异有统计学意义(P＜0. 01)。观察组患者满意度评分高于对照组, 差异有统计学意义(P＜0. 01)。两组均未见治疗相关不良反应。结论 耳穴推刮疗法可以有效缓解下肢骨折术后患者疼痛程度, 提高睡眠质量。)